Pengaruh Model Pembelajaran Kooperatif Tipe Numbered Head Together (NHT) Terhadap Hasil Belajar PKn di Kelas V SDN 09 Bandar Buat - Fauzi, Reski; Indrawati, Tin; Ahmad, Syafri (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
This research aims at finding out the effects of applying the NHT model toward the students’ learning outcomes of Civics subject at class V of SDN 09 Bandar Buat. The population of this quasi experiment research was all grade students of the school with the total number of 56 students. The samples were Class VA and VB. Data were obtained from a pretest and a posttest. They were analized by using the inferential statistics (t-test). The analysis shows that the score of tcount = 1.772 while P-Value = 0.082. Since the score P-Value is lower that α = 0.05, the H1 hypothesis is accepted. Keywords: the NHT Model, Learning Outcomes, effect, PKn